Professores alfabetizadores e a formação continuada: um estudo de caso sobre o curso instrumentos da alfabetização - Miriam Maria Roberto Marmol (2011)
This research aimed at analyzing the opinion of literacy teachers at the end a continuing education course, coordinated by Ceale (Literacy, Reading and Writing Center) at the Faculdade de Educação da Universidade Federal de Minas, using the Literacy Devices collection. In order to achieve our goals, we have used as an instrument for analyzing this course an evaluation questionnaire, answered by participant teachers from public schools of the states of Amapá, Mato Grosso do Sul, Minas Gerais, Pará, and Rondõnia. To form the analyze corpus, we have randomly chosen 182 questionnaire, that were quantitatively and qualitatively analyzed. The data from the questionnaires allowed us to create analyze categories about learning time, material used, teacher and the relation between the content offered and the pedagogical practice. This analyzes pointed out the voices from those professionals on a governmental action on continuing education. In order to found our referential on teacher education, we have used the theoretical discussions from the following researchers: Nóvoa (1992), Perrenoud (1993/2002), Tardif (2002/2008), Shon (1992), Gatti (2003/2008/2009), Diniz-Pereira (2009) and Santos (1998/2007). Since continuing education is based on the literacy area, we have dialogued, yet, with Soares (1998/2004), Frade (2010) and others authors of the Literacy Instruments Collection. The data analyzed lead us to conclude that the continuing education was satisfactory to most of the teacher enrolled concerning time, material used, and the relation between content given and pedagogical practice, and the interaction between the educator and the student. In the other hand, there are issues that still need to be solved in the continuing education: making it available to all teachers from the public school net and not only to a few; expanding the dialog, the experience exchange between different socio-cultural realities, and not only to a group of literacy teacher from a exclusively urban reality